UNSUR BUDAYA DALAM KUMPULAN CERPEN ROKAT TASE KARYA MUNA MASYARI DAN MODUL AJARNYA DI KELAS XI SMA - Nurwiyanti, Melisa; Purwanto, Joko; Setyorini, Nurul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Abstract This study aims to describe cultural elements in the short story collection Rokat Tase by Muna Masyari and compile a short story teaching module for grade XI SMA according to the Merdeka Curriculum. The method used is descriptive qualitative with interactive analysis techniques. Data were obtained from the short story collection and analyzed based on seven cultural elements according to Koentjaraningrat: language system, knowledge, livelihood, equipment and technology, art, religion, and society. The results of the study show: 1) elements of Madurese culture, such as the use of the term ghitek (small boat), the tradition of weaning children, mutual cooperation between fishermen, traditional sickle weapons, kejhungan performances, food stall businesses in the market, and the rokat tase ritual as a form of gratitude to the sea. All of these elements reflect the identity and cultural values ??of Madura. 2) The teaching module is compiled using the Problem Based Learning (PBL) learning model and contains phase F learning achievements to analyze culture in short story texts. This teaching module is expected to be able to foster cultural awareness and improve students' critical literacy skills in understanding literary works based on local culture.